Inhibiting SLC26A4 reverses cardiac hypertrophy in H9C2 cells and in rats - Tang,Liqun; Yu,Xiaoqin; Zheng,Yangyang; Zhou,Ning (PeerJ, 2020)
Background It has been confirmed that mutations in solute carrier family 26 member 4 (SLC26A4) contribute to pendred syndrome. However, the role of SLC26A4 in cardiac hypertrophy and the signaling pathways remain unclear. Methods Cardiomyocytes were treated by 200 µM phenylephrine (PE) to induce cardiac hypertrophy. Also, the expression of SLC26A4, GSK3, cardiac hypertrophy markers including atrial natriuretic peptide (ANP) and brain natriuretic peptide (BNP) was detected through real-time quantitative polymerase chain reaction (RT-qPCR). Flow cytometry assay was used to test the apoptosis of PE-induced cardiomyocytes transfected by small interfere RNA (siRNA)-SLC26A4. Furthermore, we detected the expression of autophagy-related markers including light chain 3 (LC3) and P62. Finally, we established a rat model of abdominal aortic constriction (AAC)-induced cardiac hypertrophy in vivo. Results RT-qPCR results showed that the mRNA expression of SLC26A4 was significantly up-regulated in PE-induced cardiac hypertrophy. After inhibiting SLC26A4, the release of ANP and BNP was significantly decreased and GSK3β was elevated in vivo and in vitro. Furthermore, inhibiting SLC26A4 promoted apoptosis of cardiac hypertrophy cells. In addition, LC3 was down-regulated and P62 was enhanced after transfection of siRNA-SLC26A4. Conclusion Our findings revealed that SLC26A4 increases cardiac hypertrophy, and inhibiting SLC26A4 could decrease the release of ANP/BNP and promote the expression of GSK-3β in vitro and in vivo. Moreover, SLC26A4 silencing inhibits autophagy of cardiomyocytes and induces apoptosis of cardiomyocytes. Therefore, SLC26A4 possesses potential value to be a therapeutic target of cardiac hypertrophy, and our study provides new insights into the mechanisms of cardiac hypertrophy.
Keywords: SLC26A4; Cardiac hypertrophy; Apoptosis; Autophagy; Cardiomyocytes